2019
DOI: 10.2147/lctt.s177618
|View full text |Cite
|
Sign up to set email alerts
|

<p>Polo-like kinase 1 inhibition in NSCLC: mechanism of action and emerging predictive biomarkers</p>

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer death worldwide. Due to often unspecific disease symptoms, locally advanced or metastatic disease is diagnosed in the majority of all cases. Palliative treatment options comprise of conventional cytotoxic agents, immunotherapy with checkpoint inhibitors and the use of specific small-molecule tyrosine kinase inhibitors (TKI). However, these TKIs are mainly restricted to a small proportion of patients with lung cancer that harbor activating driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Upregulation of Plk1 has been reported in several tumor types, including NSCLC. In these studies, high Plk1 expression levels correlated with poor patient prognosis, corroborating its importance in tumor progression and its potential as a therapeutic target [7][8][9][10][11]. So far, several small molecule inhibitors of Plk1 have been developed and are currently being evaluated in clinical trials.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Upregulation of Plk1 has been reported in several tumor types, including NSCLC. In these studies, high Plk1 expression levels correlated with poor patient prognosis, corroborating its importance in tumor progression and its potential as a therapeutic target [7][8][9][10][11]. So far, several small molecule inhibitors of Plk1 have been developed and are currently being evaluated in clinical trials.…”
Section: Introductionmentioning
confidence: 62%
“…So far, several small molecule inhibitors of Plk1 have been developed and are currently being evaluated in clinical trials. Volasertib, at present the lead agent in the category of Plk1 inhibitors, has been shown to induce mitotic arrest and cell death with a high efficacy in vitro, and to inhibit tumor growth in xenograft models [4,[11][12][13]. In clinical trials, volasertib has been well tolerated, and has shown encouraging antitumor activity in patients with acute myeloid leukemia (AML) [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…JUN and MYC) and are also known to have important roles in proliferation in lung epithelial cells. PLK1 is another interesting gene on the list which has been previously linked to proliferation and migration in non small cell lung cancers, a tumor type arising from lung epithelial cells [39,40].…”
Section: Activity Of Top Ranked Genes In Underlying Health Conditionsmentioning
confidence: 99%